Legal Enforcement of the National Emissions Trading Scheme and the Environmental Protection Tax in China: Heavy Hand or Light Touch?. (2nd May 2022) - Geroe, Steven; Zhang, Hao
Abstract: This article evaluates the severity of legal enforcement measures for the 2021 National Carbon Emissions Trading Management (Trial) Measures (ETS Trial Measures) and the Environment Protection Tax (EPT) as a potential model or basis for carbon taxation. While the focus is on the content of specific regulatory provisions, evidence of enforcement action forms part of their evaluation. The ETS Trial Measures are compared to the enforcement provisions in Chinese regional emission-trading scheme (ETS) pilots, the 2019 and 2020 opinion solicitation drafts (OSDs), and the March 2021 OSD for a proposed State Council regulation, drawing on the scholarly literature and interviews in the specialist Chinese government and professional and research institutions. The current ETS enforcement measures are weaker and less comprehensive than those in some pilots and in all of the OSDs. Adopting measures recommended by interviewees as effective in the pilots could augment their stringency. The EPT has a stronger basis for enforcement through existing taxation and environmental laws. While its enforcement has been backed by an increasingly centralized environmental governance system, design elements that allow regional flexibility in implementation and inconsistent enforcement have reduced its effectiveness. These outcomes may be influenced by trade-offs between central government objectives and subnational economic and industrial priorities and resistance by powerful commercial interests. These limiting factors can be addressed by effective regulatory implementation, successful trading, and combining stringent penalties with measures that have a lighter touch, such as capacity building, leading to deepening acceptance by all stakeholders.